Fundamental Right to Life: Right to Health as a Principle of Human Dignity - Melo, Rebeca de Magalhães; Araújo Magalhães Nogueira, Teresinha de Jesus (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
Abstract Human rights base themselves on the principle that “All human being are born free and with equal dignity and rights”. The Universal Declaration of Human Rights, based on this central idea, divides rights between civil, political, social and economical. This paper aims to analyze the application and guarantee of the right to live by the adequation of healthcare by the judiciary. It Questions: What leads the right to the judicializing of healthcare in Brazi? It is observed that the rights complete/intersect themselves. Human dignity pressuposes the guarantee of rights, primarily in the respect of social security, standards of living and effective adequacy of healthcare. It is urgent that there is a guarantee of the right to healthcare both in the public and private spheres, evidencing itself in the necessity of judializing due to the lack of efficient public services